Introduction to financial statements - McDonald, Michael (Henry Stewart Talks, 2019)
Basic financial statements, Balance sheet, Assets & liabilities, Owner’s equity, Income statement, Net income, Revenue & expenses, Statement of cash flows, Operating activities -Investing activities, Financing activities, Statement of retained earnings, Apple’s balance sheet, General Electric’s income statement, IBM’s cash flow statement